Fundamentals of crisis counseling - Miller, Geraldine A., 1955- (Hoboken, N.J. : John Wiley and Sons, 2012)
Fundamentals of Crisis Counseling provides practical, readily applicable theoretical and research-based crisis intervention approaches for mental health professionals and students in training. In her approachable writing style, and with case studies and exercises interwoven throughout to assist the reader in applying the models described, author Geri Miller addresses working with different ethnic and cultural groups within a broad range of crisis work. The book also includes a chapter on self-care for the mental health professional working in crisis situations, and is unique in its coverage of the use of spirituality as a crisis coping resource.
Introduction/overview -- Crisis theories, domains, and intervention models -- Disaster mental health counseling -- Settings and commonly occurring diagnoses -- Special populations and legal/ethical issues -- Assessment -- Current additional therapies and concepts -- Working with different cultures -- Self-care.
Includes bibliographical references and indexes.
Keywords: Crisis intervention (Mental health services); Counselling; Crisis Intervention; Counseling -- methods